2021
DOI: 10.1523/jneurosci.0633-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Tuba Activates Cdc42 during Neuronal Polarization Downstream of the Small GTPase Rab8a

Abstract: The acquisition of neuronal polarity is a complex molecular process that depends on changes in cytoskeletal dynamics and directed membrane traffic, regulated by the Rho and Rab families of small GTPases, respectively. However, during axon specification, a molecular link that couples these protein families has yet to be identified. In this paper, we describe a new positive feedback loop between Rab8a and Cdc42, coupled by Tuba, a Cdc42-specific guanine nucleotide-exchange factor (GEF), that ensures a single axo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…In the neuroblastoma cell line, it was demonstrated that Rab8a activity promotes Cdc42 activation through Tuba. Tuba and Rab8a also regulate the morphology of migrating neurons (Urrutia et al, 2021; Figure 3B). Aside from Rab8a, Rab35 has also been demonstrated to modulate Cdc42 activity in neurons, as Rab35-induced neurite growth dependent on Cdc42 and Rac1.…”
Section: Interactions Of Rho and Rab Proteins In Modulation Of Neuron...mentioning
confidence: 99%
See 3 more Smart Citations
“…In the neuroblastoma cell line, it was demonstrated that Rab8a activity promotes Cdc42 activation through Tuba. Tuba and Rab8a also regulate the morphology of migrating neurons (Urrutia et al, 2021; Figure 3B). Aside from Rab8a, Rab35 has also been demonstrated to modulate Cdc42 activity in neurons, as Rab35-induced neurite growth dependent on Cdc42 and Rac1.…”
Section: Interactions Of Rho and Rab Proteins In Modulation Of Neuron...mentioning
confidence: 99%
“…Similarly, suppression of Rab11 also resulted in delayed neuronal migration (Kawauchi, 2011). Both exocytic and endocytic pathways are critical for neuron differentiation, elongation of neuronal processes, and their migration (Kawauchi, 2011;Urrutia et al, 2021). Hence Cdc42 and Rab GTPases might crosstalk in modulating neuronal morphology, migration, and polarity (Kawauchi, 2011;Villarroel-Campos et al, 2016;Urrutia et al, 2021).…”
Section: Interactions Of Rho and Rab Proteins In Modulation Of Neuron...mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the small GTPase Rap1b, an upstream activator of CDC-42 is enriched in the axonal tip of stage 3 neurons, suggesting a local regulation ( Schwamborn and Püschel, 2004 ). Along this line of evidence, a recent article reported that the dynamin-binding protein (DNMBP) TUBA segregates into the axon working as GEF for CDC-42 ( Urrutia et al, 2021 ). Collectively, these observations suggest local regulations favoring CDC-42 activation in axons.…”
Section: Intrinsic Programs Supporting Polarizationmentioning
confidence: 99%